LITERATURE STUDY: THE EFFECT OF INTERACTIVE LEARNING MODELS ON THE COGNITIVE DEVELOPMENT OF ELEMENTARY SCHOOL STUDENTS - Tanjung, Risna Aini (ONTOLOGI : JURNAL PEMBELAJARAN DAN ILMIAH PENDIDIKAN, 2025)
This study investigates the impact of interactive learning models on the cognitive development of elementary school students. The study focuses on interactivity in learning and integrates a literature review to provide detailed insights into the relationship between interaction in learning and cognitive progress. The relationship between the use of interactive learning models and students' cognitive abilities was investigated using descriptive and critical analysis methods. The results indicate that interactive learning approaches strengthen the relationship between teachers and students, encourage active engagement, and enable deeper understanding. Furthermore, interaction in learning enhances students' problem-solving abilities, improves critical thinking skills, and broadens their conceptual understanding.